Evaluation and Meta-Evaluation of the Effectiveness of Victim-Oriented Legal Reform in Europe - Brienen, Marion; Hoegen, Ernestine; Groenhuijsen, Marc (Criminologie, 2000)
AbstractThe 1985 UN Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power, and the Council of Europe's Recommendation (85) 11 on the Position of the Victim in the Framework of Criminal Law and Procedure are important documents that reflect an international consensus on legal rights for victims.In many European jurisdictions, such victims' rights have been introduced or improved upon. However, they are often not used as intended or remain virtually dormant. The UN has therefore adopted a Resolution and drafted a manual on ways to facilitate effective implementation. In addition, certain jurisdictions have proved sensitive to implementation problems. The Netherlands, for example, put the new Victim Act into effect on an experimental basis in two legal districts to carefully evaluate the effects of new provisions, and to apply the resulting knowledge when expanding its territorial scope.However, more sophisticated instruments are needed to set implementation parameters at a supra-national level. To this effect, we conducted a comparative study of both a legal and empirical nature in 22 member states of the Council of Europe. The study revealed, inter alia, critical factors of failure or success. The workings of these critical factors in the implementation of Recommendation (85) 11 are demonstrated by drawing upon illustrations taken from the reality of certain jurisdictions. The examples are subdivided into four major themes: information, compensation, treatment and protection.As the second guideline of Recommendation (85) 11 expresses, the creation of a formal duty for the police to provide victims with information about the possibilities of obtaining assistance, legal aid and compensation is vital. However, in half of the jurisdictions, no such reform has been implemented. Our study reveals that critical factors of failure are, among other things, a widespread conceptualization of the victim as an alleged victim and the creation of an information duty for the judicial authorities instead of for the police. In jurisdictions where an information duty has been created, failure depends, first of all, on whether the police are content with a symbolic fulfillment of this task. Critical factors needed to improve successful implementation are the creation of organizational incentives, monitoring systems, and systematic referral to victim support, legal aid and social or counseling services. A final step to improve implementation of information duties would be financial compensation earned for victim-related activities carried out by the police and other authorities.Concerning compensation, research reveals that the compensation order, particularly the English one, is more successful than the partie civile model or the Dutch compensation measure. The most important critical factor of success of the compensation order is that it is a penal sanction, enforcable by the state. This means that civil liability is not a prerequisite and that the court can order an amount of compensation it considers appropriate while taking the financial capacity of the offender into account. Furthermore, the court is obliged to consider making a compensation order and to explain why it was not imposed. A critical factor of failure of the partie civile model is that it includes an easy escape clause: claims can be referred to civil court. A critical factor of failure of the compensation measure is that it is a penal sanction governed by civil law. In practice, it resembles the traditional partie civile model: the two are blended into one.The way victims are treated by criminal justice authorities can be improved by providing victim-awareness training. A critical factor of failure is to only train recruits. Training is only effective if it is extended to incumbent personnel. Giving refresher courses and measuring the effects of training in performance assessments are factors contributing to success. A critical factor of failure in such training for judicial authorities is the argument that it would compromise their independence.Critical factors to improve the questioning of victims are the provision of specific training courses and the creation of special facilities, e.g. interviewing studios for children, suites for victims of sexual offences, audio-video recording of pre-trial examinations and video-linked questioning. Such reform measures benefit the quality of the criminal justice process as a whole and therefore prove to be successful.A common manner of protecting victims is to allow that a trial, or a part thereof, be conducted in camera. A critical factor of failure is the (very) reluctant attitude of the judiciary toward holding a trial behind closed doors. A critical factor of success is the creation of a formal duty for the court to hold all cases involving sexual offences in camera.We can conclude that successful implementation of victim-oriented reforms depends on, inter alia, the clarity and conciseness of reform measures, the absence of easy escape clauses, the attitude of criminal justice authorities, and whether the reforms also benefit the offender and/or the criminal justice system as a whole.